Interoception and Empathy Impact Perspective Taking - Heydrich, Lukas; Walker, Francesco; Blättler, Larissa; Herbelin, Bruno; Blanke, Olaf; Aspell, Jane Elizabeth (Frontiers in Psychology, 2021)
Adopting the perspective of another person is an important aspect of social cognition and has been shown to depend on multisensory signals from own’s own body. Recent work suggests that interoceptive signals not only contribute to own-body perception and self-consciousness, but also to empathy. Here we investigated if social cognition - in particular adopting the perspective of another person - can be altered by a systematic manipulation of interoceptive cues and further, if this effect depends on empathic ability. The own-body transformation task (OBT) - wherein participants are instructed to imagine taking the perspective and position of a virtual body - offers an effective way to measure reaction time differences linked to the mental effort of taking an other’s perspective. Here, we adapted the OBT with the flashing of a silhouette surrounding the virtual body, either synchronously or asynchronously with the timing of participants’ heartbeats. Empathy was assessed with the empathy quotient questionnaire. We report that participants with high empathy showed significantly better performance during the OBT task during synchronous versus asynchronous cardio-visual stimulation. Moreover, we found a significant correlation between empathic ability and the synchrony effect (the difference in reaction times between the asynchronous and synchronous conditions). We conclude that synchronous cardio-visual stimulation between the participant’s body and a virtual body during an OBT task makes it easier to adopt the virtual body’s perspective, presumably based on multisensory integration processes. However, this effect depended on empathic ability, suggesting that empathy, interoception and social perspective taking are inherently linked.